Performance analysis of refrigerants with various expansion valves in vapour compression refrigeration and air-conditioning system. (2021) - Sivaraman, N.; Muthu Vaidyanathan, R.; Patel, Mahaboob; Markos, Mebratu
Abstract: The primary role of expansion devices in Vapour Compression Refrigeration System (VCRS) are dropping the pressure, temperature and regulates the mass flow rate of refrigerant gas concerning with evaporator load conditions. Also, proper selection of expansion devices helps to control the degree of super heat to protect the compressor from liquid slugging. The performance of the vapour compression system partially depends on the expansion devices. The different predictions such as theoretical, experimental and simulation which are carried out by various researchers on basis of design, development and selection of the expansion devices concerning with different flow conditions. The present study is describes the performance of different expansion devices involving various refrigerants gases like as R134a, hydrocarbon LPG, R600a, and R22 etc. It is also discussed with proper understanding about the recent development of various expansion devices using for different refrigerant gases.